Socio economic impact of One-Town-One-Product (OTOP) Entrepreneurial program in Region 1 Philippines - Tabisola, Christian Thom F. (The journal of contemporary issues in business and government, 2019)
One-town-one-product (OTOP) is a program of the Department of Trade and Industry that envisions having a product for each town and making it known to the market locally and internationally. This study described the socio-economic impact of OTOP entrepreneurial program as perceived by the entrepreneurs. The descriptive design was used in this study with survey questionnaire as research instrument. Most of the respondents are female, married, middle adult, and completed high school. They earned minimal profit, with few numbers of workers and started business using credit and personal money. They are prepared on creating new product standardization, regional production networks including sub-contracting process, and export procedures. Most of them agree that the OTOP program conducted activities like entrepreneurship development program of the province, and tracking of small medium readiness. When it comes to the impact of OTOP to the entrepreneurs, OTOP Region 1 provides average impact on the conduct of marketing endeavours, and better conducive business environment. The OTOP-Philippines program, in spite of its limitations, offers opportunities to thousands of rural enterprises to become viable and competitive. Therefore, it is imperative that reforms are instituted to make the program truly unleash and harness the entrepreneurship that is needed to move the Philippines forward and be readily competitive in positioning its niche for the global market penetration. In order to make the OTOP program more responsive to the needs of the entrepreneurs in Panagsinan, it is recommended that equal attention must be given in improving the production efficiencies of rural enterprises, investment in research and development, provide room for improvement in the processed food sector, accessible financing to rural micro and small enterprises, and provision of structural reforms to make sure that the business enabling environment is conducive to the creation and growth of rural enterprises.